Assessment of cumulative damage by using ultrasonic C-scan on carbon fiber/epoxy composites under thermal cycling - Shiino, Marcos Yutaka [UNESP]; Faria, Maria Candida Magalhães [UNESP]; Botelho, Edson Cocchieri [UNESP]; Oliveira, Pedro Carlos de (ABM, ABC, ABPol, 2012)
In recent years, structural composites manufactured by carbon fiber/epoxy laminates have been employed in large scale in aircraft industries. These structures require high strength under severe temperature changes of -56° until 80 °C. Regarding this scenario, the aim of this research was to reproduce thermal stress in the laminate plate developed by temperature changes and tracking possible cumulative damages on the laminate using ultrasonic C-scan inspection. The evaluation was based on attenuation signals and the C-scan map of the composite plate. The carbon fiber/epoxy plain weave laminate underwent temperatures of -60° to 80 °C, kept during 10 minutes and repeated for 1000, 2000, 3000 and 4000 times. After 1000 cycles, the specimens were inspected by C-scanning. A few changes in the laminate were observed using the inspection methodology only in specimens cycled 3000 times, or so. According to the found results, the used temperature range did not present enough conditions to cumulative damage in this type of laminate, which is in agreement with the macro - and micromechanical theory.
Keywords: carbon fiber reinforcement plastics (CFRP); ultrasonic; thermal cycling